2018
DOI: 10.1103/physrevc.98.044627
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the distorted-wave impulse-approximation description of Ca40(e,ep)K39

Abstract: The nonlocal implementation of the dispersive optical model (DOM) provides all the ingredients for distorted-wave impulse-approximation (DWIA) calculations of the (e, e ′ p) reaction. It provides both the overlap function, including its normalization, and the outgoing proton distorted wave. This framework is applied to describe the knockout of a proton from the 0d 3 2 and 1s 1 2 orbitals in 40 Ca with fixed normalizations of 0.71 and 0.60, respectively. Data were obtained in parallel kinematics for three outgo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 54 publications
(167 reference statements)
5
47
0
Order By: Relevance
“…While the use of nonlocal optical potentials may slightly increase this value as shown in Ref. [17], it may be concluded that the value of 0.69 obtained from the present analysis is completely consistent with this result. Nikhef data obtained in a large missing energy and momentum domain [54] can therefore now be consistently analyzed employing the complete DOM spectral functions.…”
Section: Dom Fit Of 208 Pbsupporting
confidence: 90%
See 2 more Smart Citations
“…While the use of nonlocal optical potentials may slightly increase this value as shown in Ref. [17], it may be concluded that the value of 0.69 obtained from the present analysis is completely consistent with this result. Nikhef data obtained in a large missing energy and momentum domain [54] can therefore now be consistently analyzed employing the complete DOM spectral functions.…”
Section: Dom Fit Of 208 Pbsupporting
confidence: 90%
“…This factor can be probed using the exclusive (e, e p) reaction as discussed in Ref. [17]. Note that because of the presence of imaginary parts of the self-energy at other energies, there is also strength located there, thus the spectroscopic factor will be less than 1 and also less than the occupation probability.…”
Section: A Single-particle Propagatormentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [9], a nonlocal dispersive optical model (DOM) which simultaneously describes both bound and scattering states was used to consistently provide all ingredients, including spectroscopic factors, for an accurate DWIA description of 40 Ca(e, e p) 39 K data.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate this discrepancy, a consistent DWIA analysis of 48 Ca(e, e p) 47 K is performed using a nonlocal DOM description similar to the one reported in Ref. [9] for 40 Ca. Comparing the DOM calculated spectroscopic factors of 48 Ca and 40 Ca will provide more information on the quenching of proton spectroscopic factors when neutrons are added.…”
Section: Introductionmentioning
confidence: 99%